Case Fatality Risk of the First Pandemic Wave of Coronavirus Disease 2019 (COVID-19) in China. (15th May 2020) - Deng, Xiaowei; Yang, Juan; Wang, Wei; Wang, Xiling; Zhou, Jiaxin; Chen, Zhiyuan; Li, Jing; Chen, Yinzi; Yan, Han; Zhang, Juanjuan; Zhang, Yongli; Wang, Yan; et al.
Abstract: Background: To assess the case fatality risk (CFR) of COVID-19 in mainland China, stratified by region and clinical category, and estimate key time-to-event intervals. Methods: We collected individual information and aggregated data on COVID-19 cases from publicly available official sources from 29 December 2019 to 17 April 2020. We accounted for right-censoring to estimate the CFR and explored the risk factors for mortality. We fitted Weibull, gamma, and log-normal distributions to time-to-event data using maximum-likelihood estimation. Results: We analyzed 82 719 laboratory-confirmed cases reported in mainland China, including 4632 deaths and 77 029 discharges. The estimated CFR was 5.65% (95% confidence interval [CI], 5.50–5.81%) nationally, with the highest estimate in Wuhan (7.71%) and lowest in provinces outside Hubei (0.86%). The fatality risk among critical patients was 3.6 times that of all patients and 0.8–10.3-fold higher than that of mild-to-severe patients. Older age (odds ratio [OR], 1.14 per year; 95% CI, 1.11–1.16) and being male (OR, 1.83; 95% CI, 1.10–3.04) were risk factors for mortality. The times from symptom onset to first healthcare consultation, to laboratory confirmation, and to hospitalization were consistently longer for deceased patients than for those who recovered. Conclusions: Our CFR estimates based on laboratory-confirmed cases ascertained in mainland China suggest that COVID-19 is more severe than the 2009 H1N1 influenza pandemic in hospitalized patients, particularly in Wuhan. Our study provides a comprehensive picture of the severity of the first wave of the pandemic in China. Our estimates can help inform models and the global response to COVID-19. Abstract : We used publicly available data to assess the case fatality risk of COVID-19 in mainland China, stratified by region and clinical category. The case fatality risk was highest in Wuhan and increased with age, being male, and clinical severity.